Causes of student’s poor performance in business studies at advanced level from the period 2015 to 2017: a case study of Nhedziwa High and Ndima government high schools in Chimanimani district of Manicaland province - Mwandihamba, Praise (Midlands State University, 2018)
The purpose of this study was to find the causes of student poor performance in A’ level Business Studies at two selected high schools, which are in Chimanimani District of Manicaland province. The study sought to explore the challenges faced by both students and educators in the teaching and learning of Business Studies at A’ level which results in poor student’s performance. Both home environmental factors and the school environmental factors were looked upon as target areas. Prior to the collection of data for the research, a review of related literature was done by the researcher. Multiple case study design was employed in this research study. It facilitates the exploration of a phenomenon within its real life context using a variety of data sources. The population for this study comprised of all 65 A’ level Business studies students ( 35 at Nhedziwa and 3o at Ndima Government High Schools), 14 A’ level teachers (7 from each school), two school heads and 65 A’ level students’ parents. The research sample was made up of 45 participants. Among those students doing Business studies at advanced level, the researcher used a sample of 15 students from each of the 2 schools used for the study, School heads and 7 teachers (4 from one school) and 3 parents of the sampled A’ level students from each school. Purposive sampling technique was used to select school heads and Business Studies teachers as well as parents. Students were selected using the simple random sampling where by each individual had an independent chance of being selected. The data collection instruments which were used in this study included both closed and open ended questionnaires, and structured and unstructured interviews. Parents and school heads were interviewed on why teachers and students answered questionnaires. The findings revealed that there were numerous factors at home and at school contributing to the poor performance of A’ level Business Studies Students. Key findings of this research suggest that the home environment of learners is not educationally encouraging due to poverty, which includes factors such as high unemployment rate, parents’ level of education, and unpredictable home environment. In the school environment, the study showed the following causative factors: lack of resources, inadequate learner support materials, teacher to student ration, lack of teachers motivation, teaching and learning strategies, teachers qualification, teachers experience and lack of interest in students. As a result, the study concluded that both school and home environment factors work together in producing poor performance in the schools. These findings were presented in forms of frequency tables, pie charts and bar graphs. Recommendations are supported and they include provision of adequate teaching and learning resources, relevant textbooks, qualified teachers, income generating projects like Agriculture and library to improve the performance in the subject. Also parents and teachers should work together in creating a conducive environment for students to enhance their learning.